Involvement of the DnaK-DnaJ-GrpE chaperone team in protein secretion in Escherichia coli. - Wild, J (1996)
We used depletion studies designed to further investigate the role of the DnaK, DnaJ, and GrpE heat shock proteins in the SecB-dependent and SecB-independent secretion pathways. Our previous finding that SecB-deficient strains containing the grpE280 mutation were still secretion proficient raised the possibility that GrpE was not involved in this secretory pathway. Using depletion studies, we now demonstrate a requirement for GrpE in this pathway. In addition, depletion studies demonstrate that while DnaK, DnaJ, and GrpE are involved in the secretion of the SecB-independent proteins (alkaline phosphatase, ribose-binding protein, and beta-lactamase), they are not the primary chaperones in this process.